Arab Spring, Islamist Ice Age: Islamism, Democracy, and the Dictatorship of the “Liberalism of Fear” in the Era of Revolutions (American Journal of Islam and Society, 2013)
Between June 30th, the twenty-fourth anniversary of the Islamist military takeoverin Sudan, and July 4th, Independence Day in the United States, somethingmiraculous happened in the Middle East. Suddenly everyone was in agreement,and – almost – everyone was happy. President Bashar al-Assad was ecstatic.In an interview with the Baath Party’s newspaper Al-Thawra shortly after thearmy deposed Muhammad Morsi, Egypt’s first-ever freely elected civilian president,on July 3, Assad applauded the coup as marking “essentially the fall ofpolitical Islam.”1 In his lengthy interview, he categorized his enemies into twogroups: those “who completely abandoned their identity and embraced a ‘WesternDream’ even with all its flaws” and those “who went in exactly the oppositedirection and abandoned their identity and embraced religious extremism.”2The latter he alternatively designated as “Wahhabis” or “Takfiris.”In the presumed bastions of Wahhabism in the Gulf, Morsi’s downfallwas received with even more elation. Within days, Saudi Arabia, Kuwait, andthe UAE pledged an aid package worth USD 12 billion to cash-strappedEgypt, showing how much they appreciated this outcome.3 And while Israeljoined its sworn enemy Hamas in maintaining a guarded silence,4 its media(and some politicians) did not hide their glee at Morsi’s political demise.5As usual, the Obama administration was either unable to make up its mindor was too embarrassed to say what it believed. But that was in itself a clearstance, since the United States was happy to permit its key allies to providemassive cash injections to the new army-backed regime. It also refrained from ...